Pharmaceutical aspects of silver nanoparticles. (31st October 2018) - Mathur, Prateek; Jha, Swati; Ramteke, Suman; Jain, N. K.
Abstract: Silver nanoparticles are particles in the size ranging between 1 and 100 nm. The two major methods used for synthesis of silver nanoparticle are the physical and chemical methods with the disadvantage that they are expensive and can also have toxicity. Biological method is being used as an expedient alternative, as this approach is environment-friendly and less toxic and it includes plant extracts, microorganism, fungi, etc. The major applications of silver nanoparticles in the medical field include diagnostic applications and therapeutic applications, apart from its antimicrobial activity. Due to their nanotoxicity, AgNPs have a several drawbacks too. This review presents a complete view of the mechanism of action, synthesis, the pharmacokinetics of silver nanoparticles, different formulations of AgNPs used in biomedical applications, infertility management, antibacterial effects, skin damage, burns, cancer treatment, etc. and various applications of silver nanoparticles together with the possible toxicological challenge.